Peran Manajemen Guru Dalam Meningkatkan Mutu Pembelajaran di TK Aulia School - Elya Siska Anggraini; Citra Alsya Ayudia; Dewinta Sari; Diva Amalia; Paulus Novento; Qamara Ayu; Salfa Suzhi Sahna Pramesty; Triaksha Debora (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
This study aims to examine the role of teacher management in enhancing learning quality at TK Aulia School. A phenomenological approach with descriptive qualitative methods was employed. Data were collected through interviews, observation, and documentation. The findings reveal that teachers play a central role in designing, implementing, and evaluating learning activities that are enjoyable and developmentally appropriate. The use of daily lesson plans (RPPH), individualized approaches, and flexible classroom management contribute to a positive learning environment. Teachers address the unique needs of each child by providing personal attention and adapting instructional strategies accordingly. Collaboration with parents is fostered through regular progress reports and school committee meetings. Additionally, continuous professional development, including training on child protection and health issues, supports teachers’ capacity to improve learning outcomes. The structured and ongoing teacher management system has proven effective in fostering a holistic and engaging educational experience for early childhood learners. These results highlight the essential role of teacher management in improving the overall quality of early childhood education and recommend its integration into broader educational development strategies.